Ethio‑Djiboutian Relations in the 21st century – towards New African Cooperation - Joanna Mormul (Ksiegarnia Akademicka Publishing, 2021)
Very good political and economic relations between Djibouti and Ethiopia can be treated as an exceptional case in such a conflict‑ridden region as the Horn of Africa. Ethio‑Djiboutian cooperation owes its ‘renaissance’ mostly to the consequences of the Eritrean‑Ethiopian War (1998‑2000) that left Ethiopia without direct access to a sea basin. Today, almost 90 per cent of Ethiopia’s imports arrive via the port of Djibouti, while Ethiopia receives 95 per cent of the Djiboutian regional exports. One of the major infrastructure projects that should even enhance this interstate cooperation is the renovation of the Addis Ababa‑Djibouti railway network. On the international level both countries are committed to the question of security, peace, and stability in the Horn of Africa (e.g. they are engaged in Somali and South Sudanese peace processes). The aim of the article is to analyze this specific personification of interstate cooperation, taking into account the conceptual framework imposed by the definition of ‘interstate cooperation’ proposed by Robert Keohane back in the 1980s. Moreover, the author attempts to look into the reasons behind the development of such good relations, seeking an answer to the question whether or not they are really mutually beneficial .